The Design of The Tuk-Tuk Lakeside Resort Lake Toba (Green Architecture) (International Journal of Architecture and Urbanism, 2020)
The high number of tourists who come to visit during the holiday season comes to Samosir Island. However, the number of tourists who come to the island of Samosir and the number of accommodations available at this time have not been able to meet the high interest of visiting tourists. The design of the Tuk-Tuk Lakeside Lake Toba Resort is one way to help achieve the benefit of tourists visiting the current Samosir island for comfortable lodging facilities and still feel what it is like to return to nature. The research methodology begins with collecting data, studying literature, surveying the location of the research, and also designing problem-solving. In creating an object to be designed, the designer can carry out a variety of alternative design approaches, one of which is to approach the theme that will be used in the designation, Green Architecture. The selection of Green Architecture themes in buildings is considered capable of describing functions and describing culture. Approach to the idea that takes air circulation systems that do not use the air conditioner or ac that is applied to the main buildings of hotels, restaurants, and resorts. Air and contour on the land on the plains of the unspoiled island of Samosir can become local wisdom that can be utilized in designing Tuk-Tuk lakeside Danau Toba Resort.